2003
DOI: 10.1016/s0950-0618(03)00046-1
|View full text |Cite
|
Sign up to set email alerts
|

RC column strengthening by lateral pre-tensioning of FRP

Abstract: This paper presents a unique strengthening technique for existing concrete columns that uses expansive materials to apply lateral pre-tensioning. The technique increases the capacity and ductility of a column as well as achieving better utilisation of the confining FRP (Fibre Reinforced Polymer) material. The confinement material properties and the confined cylinder performance are investigated experimentally. From the results it is shown that it is possible to control the degree of applied pre-tension by cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 6 publications
1
28
0
2
Order By: Relevance
“…In a study of concrete column strengthening by lateral pretensioning of FRPC, it was found that pretensioned FRPC materials can increase the load bearing capacity up to 35% compared with no pretensioning (Mortazavi et al, 2003). Although works on the pretension of FRPC in pipeline rehabilitation are scarce, the effect of pretension on patch repairs of steel and concrete columns has been investigated in multiple studies.…”
Section: Further Studies On Wrap Tensionmentioning
confidence: 99%
“…In a study of concrete column strengthening by lateral pretensioning of FRPC, it was found that pretensioned FRPC materials can increase the load bearing capacity up to 35% compared with no pretensioning (Mortazavi et al, 2003). Although works on the pretension of FRPC in pipeline rehabilitation are scarce, the effect of pretension on patch repairs of steel and concrete columns has been investigated in multiple studies.…”
Section: Further Studies On Wrap Tensionmentioning
confidence: 99%
“…13 (b). Thus, stresses produced in confi ning steel tube are calculated by (4) where, σ θ , σ z are circumferential stress and longitudinal stress in steel tube, respectively and ε θ , ε z the circumferential strain and axial strain obtained from the strain gauges attached on outer side of the steel tube. E s , u s the modulus of elasticity and Poisson's ratio of steel tube, respectively.…”
Section: Self-stresses In the Concretementioning
confidence: 99%
“…Expansive concrete is proven to be one of the most effective ways of overcoming this shortcoming. Expensive concrete has the special functions in building engineering and become more popular in recent decades [1][2][3][4][5][6] . Two basic classes for expansive concrete are shrinkage compensating-concrete and self-stressing concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Applying active confinement to the concrete leads to an improvement in its compressive behavior in terms of strength and ductility. Currently, there are various methods for prestressing the confining devices (Feeser, Chinn 1962;Martin 1968;KrstulovicOpara, Thiedeman 2000;Mortazavi et al 2003;Mokari, Moghadam 2008;Shinohara 2008;Chang et al 2009;Janke et al 2009;Moghaddam et al 2010;Tran et al 2015).…”
Section: Introductionmentioning
confidence: 99%